2023
DOI: 10.1002/csr.2500
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of tenure diversity on boardroom and corporate carbon emission performance: Exploring from the moderating role of corporate innovation

Abstract: This paper examines the relationship between tenure diversity, corporate innovation, and carbon emission performance in developing countries, with a particular focus on the interaction model of corporate innovation in the nexus. The study is conducted in a unique setting of Indonesian firms with a high level of tenure diversity and carbon performance, excluding the financial industry from 2015 to 2021 and covering 1466 firm‐year observations. The study confirms that tenure diversity in the boardroom is a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The control variables were selected based on previous research, including the number of directors (DIRSIZE) (Roiston & Harymawan, 2022), number of commissioners (COMSIZE) (Guan et al, 2016;Ningsih et al, 2021), and independent directors (INDCOM) (Muttakin et al, 2018) to represent good corporate governance. Firm size (FIRMSIZE) (Abdullah et al, 2023) and leverage (LEV) (Cahyono, Harymawan, & Kamarudin, 2023) were chosen to represent company characteristics, while return on assets (ROA) (Ningsih et al, 2021) and loss (LOSS) were selected as profitability ratios to represent company performance, as in Guan et al (2020). The definitions of the variables used in this study for further information are listed in Table 2.…”
Section: Data and Research Methodologymentioning
confidence: 99%
“…The control variables were selected based on previous research, including the number of directors (DIRSIZE) (Roiston & Harymawan, 2022), number of commissioners (COMSIZE) (Guan et al, 2016;Ningsih et al, 2021), and independent directors (INDCOM) (Muttakin et al, 2018) to represent good corporate governance. Firm size (FIRMSIZE) (Abdullah et al, 2023) and leverage (LEV) (Cahyono, Harymawan, & Kamarudin, 2023) were chosen to represent company characteristics, while return on assets (ROA) (Ningsih et al, 2021) and loss (LOSS) were selected as profitability ratios to represent company performance, as in Guan et al (2020). The definitions of the variables used in this study for further information are listed in Table 2.…”
Section: Data and Research Methodologymentioning
confidence: 99%
“…Board gender diversity has been reported to positively affect a company's environmental decisions (Van Hoang et al, 2021) and its plans to reduce emissions (Cicchiello et al, 2021;Haque, 2017). The diversity of the board determines the company's overall tendency toward implementing green governance activities (Cahyono et al, 2023). Qiu et al (2022) demonstrated that the existence of female directors has a significant effect on companies' decisions and that the higher the number of female directors, the higher the ESG performance.…”
Section: Board Gender Diversity Emission Reduction Targets and Carbon...mentioning
confidence: 99%
“…Specifically, auditors from specific ethnic backgrounds may have a market advantage in providing high-quality and cost-effective audit services. However, the Indonesian audit market operates under a unique audit mechanism, necessitating further exploration of the impact of auditor ethnicity on the determination of audit fees Cahyono et al . (2023).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%